Grand illusions : American art and the First World War - Lubin, David M. (Oxford University Press, 2016)
"Taking readers on a tour of the major historical events during and immediately after World War I, Grand Illusions considers the famous and forgotten artists and artworks that sought to make sense of America's first total war"--